ANALYSIS OF FACTORS AFFECTING TOURISM BUSINESS ENGAGEMENT ON INSTAGRAM SOCIAL MEDIA - Zulfikar Fauzi; Rita Komaladewi; Deru R. Indika (Jurnal Manajemen dan Bisnis Performa, 2025)
The rapid growth of social media has significantly transformed marketing strategies in the tourism industry, enabling businesses to engage directly with potential visitors. However, determining the most effective media type, posting time, and content strategy to maximize engagement remains a key challenge for tourism-related enterprises. This study aims to identify and analyze the combination of media formats, publication times, and content types that generate the highest engagement on the Instagram account @villakancil, a tourism accommodation business. Using a case study approach combined with an experimental design and supported by descriptive qualitative analysis, the research systematically tested different media formats (video and images), posting schedules (business hours and after-hours; weekdays and weekends), and content categories (informative and entertainment). The findings indicate that video content consistently achieves higher engagement than still images, posting after-hours outperforms business hours, weekdays outperform weekends, and informative content attracts more interaction than entertainment content. These results provide practical guidance for tourism marketers to optimize social media strategies and contribute to the theoretical understanding of engagement dynamics in tourism-focused digital marketing.